Frontispiece: Bioorthogonal Uncaging of the Active Metabolite of Irinotecan by Palladium‐Functionalized Microdevices. Issue 63 (15th November 2018) - Adam, Catherine; Pérez‐López, Ana M.; Hamilton, Lloyd; Rubio‐Ruiz, Belén; Bray, Thomas L.; Sieger, Dirk; Brennan, Paul M.; Unciti‐Broceta, Asier
Abstract : Systemic side effects limit the efficacy of chemotherapy regimens. To reduce toxicity, a metabolically stable prodrug of SN‐38 (irinotecan's active metabolite) has been designed to be exclusively activated by Pd‐functionalized microdevices that can be implanted into tumors. It is also shown the first concomitant uncaging of two drugs used in clinical combinations by the same bioorthogonal method. More information can be found in the Full Paper by P. M. Brennan, A. Unciti‐Broceta, et al. on page 16783 ff.